2015
DOI: 10.1097/ico.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Corneal Ring Implants

Abstract: Purpose:To evaluate the biomechanics of corneal ring implants by providing a related mathematical theory and biomechanical model for the treatment of myopia and keratoconus.Methods:The spherical dome model considers the inhomogeneity of the tunica of the eye, dimensions of the cornea, lamellar structure of the corneal stroma, and asphericity of the cornea. It is used in this study for calculating a strengthening factor sf for the characterization of different ring-shaped corneal implant designs. The strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 29 publications
1
49
0
5
Order By: Relevance
“…One explanation for the stop of progression of keratoconus after MyoRing implantation may be found in the biomechanics of the cornea before and after MyoRing implantation 15 . Since the MyoRing is a continuous full ring implant, with no disruption of continuity along its circumference, it acts in the cornea like a second (artificial) limbus and supports the cornea biomechanically in much the same way as a ceiling beam supports the ceiling of a room under load by separating the ceiling (cornea) into two compartments and reducing the load on each compartment 15 . Specifically, the MyoRing is able to take up a significant amount of the load acting on the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the stop of progression of keratoconus after MyoRing implantation may be found in the biomechanics of the cornea before and after MyoRing implantation 15 . Since the MyoRing is a continuous full ring implant, with no disruption of continuity along its circumference, it acts in the cornea like a second (artificial) limbus and supports the cornea biomechanically in much the same way as a ceiling beam supports the ceiling of a room under load by separating the ceiling (cornea) into two compartments and reducing the load on each compartment 15 . Specifically, the MyoRing is able to take up a significant amount of the load acting on the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Daxer calculated the strengthening factor for the characterization of different ring-shaped corneal implant designs and concluded that the small lamellar incision during the pocket creation technique does not affect the biomechanical stability of the corneal tissue [ 12 ]. In addition, the geometry of the complete ring with full mechanical strength of the material along the entire circumference may be biomechanically considered as a further (artificial) limbus, in contrast to ring segments, because their incomplete ring geometry has no strengthening effect on the cornea [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports demonstrated that ring segments have the disadvantage of resulting in loss of visual acuity in the long term [ 9 , 10 ]. In contrast, it was reported that MyoRing implantation itself may stop the progression of disease due to the continuous ring shape design and its ability to strengthen the biomechanical property of cornea, and its ability to stabilize the corneal thickness [ 2 , 11 ], e.g., Daxer in his study found that for ring segments and incomplete rings, the strengthening factor was 1.0 and that a intracorneal continuous complete ring (MyoRing) had a strengthening factor of up to = 3.2, because it is a continuous full-ring implant, with no disruption of continuity along its circumference, suggesting that it may act as an artificial limbus and provide biomechanical support to the cornea [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Имплантация MyoRing -это индивидуализированный подход в лечении кератоконуса посредством контроля положения кольца, а также его диаметра и толщины. Основным преимуществом имплантации интрастромальных роговичных колец является повышение НКОЗ непосредственно после операции и сохранение ее стабильности в течение следующих 24 месяцев [13]. В сроки от 6 месяцев до 1 года у ряда пациентов острота зрения может варьировать, что может быть связано как с прогрессированием основного заболевания, так и с аккомодационной нагрузкой при гиперкоррекции.…”
Section: Discussionunclassified
“…В то же время другие авторы считают, что имплантация MyoRing может остановить прогрессирование заболевания благодаря непрерывному дизайну формы кольца и его способности усиливать биомеханические свойства роговицы и стабилизировать ее толщину [2,12]. Так, А. Даксер установил, что для кольцевых сегментов и неполных колец коэффициент укрепления составляет 1,0, а для интрастромального непрерывного цельного кольца MyoRing -3,2, которое функционирует как искусственный лимб и обеспечивает биомеханическую поддержку роговицы [13,14]. Автор указал, что после имплантации MyoRing значительного прогрессирования кератоконуса не наблюдалось в течение 5 лет [14].…”
Section: Introductionunclassified